Ôn tập toán 8

Đinh Tuấn Việt

Phân tích thành nhân tử theo phương pháp nhóm hạng tử :

a) x3 - x2 - 5x + 125

b) x3 + 2x2 - 6x - 27

c) 12x3 + 4x2 - 27x - 9

Lightning Farron
12 tháng 8 2016 lúc 22:32

a) x3 - x2 - 5x + 125

=(x3-6x2+25x)+(5x2-30x+125)

=x(x2-6x+25)+5(x2-6x+25)

=(x+5)(x2-6x+25)

b) x3 + 2x2 - 6x - 27

=x3+5x2+9-3x2-15x-27

=x(x2+5x+9)-3(x2+5x+9)

=(x-3)(x2+5x+9)

c) 12x3 + 4x2 - 27x - 9

=4x2(3x+1)-9(3x+1)

=(4x2-9)(3x+1)

=[(2x)2-32](3x+1)

=(2x-3)(2x+3)(3x+1)

 

Trần Việt Linh
12 tháng 8 2016 lúc 22:35

a) \(x^3-x^2-5x+125\)

\(=\left(x^3+125\right)-\left(x^2+5x\right)\)

\(=\left(x+5\right)\left(x^2-5x+25\right)-x\left(x+5\right)\)

\(=\left(x+5\right)\left(x^2-5x+25-x\right)=\left(x+5\right)\left(x^2-6x+25\right)\)

b) \(x^3+2x^2-6x-27\)

\(=\left(x^3-27\right)+\left(2x^2-6x\right)\)

\(=\left(x-3\right)\left(x^2+3x+9\right)+2x\left(x-3\right)\)

\(=\left(x-3\right)\left(x^2+3x+9+2x\right)\)

\(=\left(x-3\right)\left(x^2+5x+9\right)\)

c) \(12x^3+4x^2-27x-9\)

\(=4x^2\left(3x+1\right)-9\left(3x+1\right)\)

\(=\left(3x-1\right)\left(4x^2-9\right)=\left(3x-1\right)\left(2x-3\right)\left(2x+3\right)\)

Hà Phương
12 tháng 8 2016 lúc 22:46

a) \(x^3-x^2-5x+125\)

\(=\left(x+5\right)\left(x^3-5x+25\right)-x\left(x+5\right)\)

\(=\left(x+5\right)\left(x^3-5x+25-x\right)\)

\(=\left(x+5\right)\left(x^3-6x+25\right)\)

Hà Phương
12 tháng 8 2016 lúc 22:30

a) \(x^3-x^2-5x+125\)

\(=\left(5+x\right)\left(25-5x+x^2\right)-x\left(5+x\right)\)

\(=\left(5+x\right)\left(25-5x+x^2-x\right)\)

\(=\left(5+x\right)\left(25-4x+x^2\right)\)

Hà Phương
12 tháng 8 2016 lúc 22:34

b) \(x^3+2x^2-6x-27\)

\(=\left(x-3\right)\left(x^3+3x+9\right)+2x\left(x-3\right)\)

\(=\left(x-3\right)\left(x^3+3x+9+2x\right)\)

\(=\left(x+3\right)\left(x^3+5x+9\right)\)

Nguyễn Phương HÀ
12 tháng 8 2016 lúc 22:37

a) x3 - x2 - 5x + 125

=\(x^3+5x^2-6x^2-30x+15x+125\)

=\(\left(x+5\right)\left(x^2-6x+15\right)\)

b) x3 + 2x2 - 6x - 27

=\(x^3-3x^2+5x^2-15x-9-27\)

=\(\left(x-3\right)\left(x^2+5x-9\right)\)

c) 12x3 + 4x2 - 27x - 9

=\(\left(x-\frac{3}{2}\right)\left(x+\frac{1}{3}\right)\left(x+\frac{3}{2}\right)\)

=\(\)

Hà Phương
12 tháng 8 2016 lúc 22:43

c) \(12x^3+4x^2-27x-9\)

\(=12x^3+\left(2x\right)^2-3^3x-3^2\)

\(=\left(2x-3\right)\left(2x+3\right)+3\left(2^2.x^3-3^2x\right)\) 

\(=\left(2x-3\right)\left(2x+3\right)+3\left\{x\left[\left(2x\right)^2-3^2\right]\right\}\)

\(=\left(2x-3\right)\left(2x+3\right)+3x\left(2x-3\right)\left(2x+3\right)\)

\(\left(2x-3\right)\left(2x+3\right)\left(3x+1\right)\)

 


Các câu hỏi tương tự
Nguyễn Ngọc Phượng
Xem chi tiết
Phương
Xem chi tiết
Võ Lê Thanh Yến
Xem chi tiết
Nguyễn Quốc An
Xem chi tiết
le thi thuy trang
Xem chi tiết
Lê Khánh Hà
Xem chi tiết
bella nguyen
Xem chi tiết
bella nguyen
Xem chi tiết
bella nguyen
Xem chi tiết